Ideal personhood through the ages: tracing the genealogy of the modern concepts of wellbeing - Joshanloo, Mohsen; Weijers, Dan (Frontiers in Psychology, 2024)
This inquiry traces the recent history of modern conceptualizations of personhood and well-being. It explores a general transition from traditional frameworks emphasizing social embeddedness, external obligations, and cosmic meaning to modern views privileging selfdetermination, authenticity, and self-expression. The inquiry shows that contemporary conceptions of well-being have emerged in Western cultures through the gradual accumulation of influences, including the Enlightenment ethos, liberal ideals, romanticism, existentialism, countercultural movements, and modern psychology. The important role of 'authenticity' is examined as a central value in contemporary well-being discourse, aligning with the modern conception of personhood. It is argued that contemporary perspectives tend to position the ideal of authentic self-fulfillment as an overarching paradigm that integrates self-determination, self-discovery, willful self-authoring, and creative identity expression. It is also argued that the widespread public support of the authentic self-actualization model in the contemporary era is partly due to the success of humanistic and positive psychology. This model's prevalence is particularly notable in regions where the modern concepts of personhood prevail, i.e., in Western cultures and, to a somewhat lesser extent, within affluent non-Western cultures. By shedding light on the Western origins of modern concepts of wellbeing, this inquiry challenges their assumed universality.